2021
DOI: 10.1007/s11548-021-02458-2
|View full text |Cite
|
Sign up to set email alerts
|

Advancing intraoperative magnetic tracing using 3D freehand magnetic particle imaging

Abstract: Purpose Sentinel lymph node biopsy is a routine procedure for nodal staging in penile cancer. Most commonly, this procedure is guided by radioactive tracers, providing various forms of preoperative and intraoperative guidance. This is further extended with fluorescence imaging using hybrid radioactive–fluorescence tracers. Alternatively, a magnetic-based approach has become available using superparamagnetic iron-oxide nanoparticles (SPIONs). This study investigates a novel freehand magnetic parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Alternative to registration of preoperative images to the patient, intraoperative tracking and interventional modalities using exogenous fiducials, can help register the output of an imaging modality to a specific anatomical location in the patient; a concept used to generate so-called freehand scans. Freehand options have been reported for US [ 169 ], beta particles [ 170 ], gamma-ray [ 171 ], fluorescence [ 172 ], and magnetic signals [ 173 ], and have been utilized in both open and laparoscopic/robotic surgery [ 174 ]. Unique for open surgery applications is that larger detectors can be used (e.g., hand-held gamma cameras [ 175 ]) and that the rotational movement in general allows for better coverage.…”
Section: Resultsmentioning
confidence: 99%
“…Alternative to registration of preoperative images to the patient, intraoperative tracking and interventional modalities using exogenous fiducials, can help register the output of an imaging modality to a specific anatomical location in the patient; a concept used to generate so-called freehand scans. Freehand options have been reported for US [ 169 ], beta particles [ 170 ], gamma-ray [ 171 ], fluorescence [ 172 ], and magnetic signals [ 173 ], and have been utilized in both open and laparoscopic/robotic surgery [ 174 ]. Unique for open surgery applications is that larger detectors can be used (e.g., hand-held gamma cameras [ 175 ]) and that the rotational movement in general allows for better coverage.…”
Section: Resultsmentioning
confidence: 99%
“…The result of premixing ICG with the commercially available magnetic tracer “Magtrace” (Endomag, Cambridge, UK) has been briefly described elsewhere 30 . In this instance, premixing created a non‐covalent binding of ICG to the carboxydextran coating of Magtrace nanoparticles, resulting in a concurrence between fluorescent and magnetic signals 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, initial results indicated that magnetometer-guided DSNB using superparamagnetic iron oxide nanoparticles was a feasible, radiation-free technique for the identification of SLNs in penile cancer ( 57 , 58 ). Another recent study investigated the use of intraoperative freehand magnetic particle imaging together with a hybrid indocyanine green–superparamagnetic iron oxide nanoparticle tracer for intraoperative SLN detection ( 59 ). The feasibility of this method was confirmed in ex vivo human skin transplants and in a porcine model, but the results need to be verified in human patients.…”
Section: Discussionmentioning
confidence: 99%